Initial blood pressure is associated with stroke severity and is predictive of admission cost and one-year outcome in different stroke subtypes: a SRICHS registry study. Issue 1 (December 2016) - Liu, Chi-Hung; Wei, Yi-Chia; Lin, Jr-Rung; Chang, Chien-Hung; Chang, Ting-Yu; Huang, Kuo-Lun; Chang, Yeu-Jhy; Ryu, Shan-Jin; Lin, Leng-Chieh; Lee, Tsong-Hai
Abstract Background To investigate if initial blood pressure (BP) on admission is associated with stroke severity and predictive of admission costs and one-year-outcome in acute ischemic (IS) and hemorrhagic stroke (HS). Methods This is a single-center retrospective cohort study. Stroke patients admitted within 3 days after onset between January 1st and December 31st in 2009 were recruited. The initial BP on admission was subdivided into high (systolic BP ≥ 211 mmHg or diastolic BP ≥ 111 mmHg), medium (systolic BP 111–210 mmHg or diastolic BP 71–110 mmHg), and low (systolic BP ≤ 110 mmHg or diastolic BP ≤ 70 mmHg) groups and further subgrouped with 25 mmHg difference in systole and 10 mmHg difference in diastole for the correlation analysis with demographics, admission cost and one-year modified Rankin scale (mRS). Results In 1173 IS patients (mean age: 67.8 ± 12.8 years old, 61.4 % male), low diastolic BP group had higher frequency of heart disease (p =0.001), dehydration (p =0.03) and lower hemoglobin level (p <0.001). The extremely high and low systolic BP subgroups had worse National Institutes of Health Stroke Scale (NIHSS) score (p =0.03), higher admission cost (p <0.001), and worse one-year mRS (p =0.03), while extremely high and low diastolic BP subgroups had higher admission cost (p <0.01). In 282 HS patients (mean age: 62.4 ± 15.4 years old, 60.6 % male), both low systolic and diastolic BP groups had lower hemoglobin level (systole:p =0.05; diastole:p <0.001). The extremely high and low BP subgroups had worse NIHSS score (p =0.01 andp <0.001, respectively), worse one-year mRS (p =0.002 andp =0.001, respectively), and higher admission cost (diastole:p <0.002). Conclusions Stroke patients with extremely high and low BP on admission have not only worse stroke severity but also higher admission cost and/or worse one-year outcome. In those patients with low BP, low admission hemoglobin might be a contributing factor.